Doping induced dielectric anomaly below the Curie temperature in molecular ferroelectric diisopropylammonium bromide - Kaige Gao (Royal Society Open Science, 2018)
A dielectric anomaly induced by doping has been observed at about 340 K in chlorine-doped diisopropylammonium bromide. The dielectric anomaly has a switchable behaviour, which indicates potential applications on switches and sensors. Temperature-dependent Raman spectrum, X-ray diffraction and differential scanning calorimetry do not show any anomaly around the dielectric anomaly temperature, which prove that the dielectric anomaly does not come from structure phase transition and has no specific heat variety. It is assumed that this dielectric anomaly can be attributed to the freezing of ferroelectric domain walls induced by the pinning of point defects.